The political economy of public investment - Beetsma, Roel M. W. J.; Ploeg, Frederick van der, 1956-; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
The political distortions in public investment projects are investigated within the context of a bipartisan political economy framework. The role of scrapping and modifying projects of previous governments receives special attention. The party in government has an incentive to overspend on large ideological public investment projects in order to bind the hands of its successor. This leads to a bias for excessive debt, especially if the probability of being removed from office is large. These political distortions have implications for the appropriate format of a fiscal rule. A deficit rule, like the Stability and Growth Pact, mitigates the overspending bias in ideological investment projects and improves social welfare. The optimal second-best restriction on public debt exceeds the level of public debt that would prevail under the socially optimal outcome. Social welfare may be boosted even more by appropriate investment restrictions: with a restriction on (future) investment in ideological projects, the current government perceives a large benefit of a debt reduction. However, debt and investment restrictions are not needed if investment projects only have a financial return.
Economic Papers